AN EXPERIMENTAL STUDY IN ENGLISH LANGUAGE TEACHING: STUDENTS’ VOCABULARY BY AUTHENTIC MATERIAL - Munawir, Ahmad; Musdalifah; Idman, Muhajirah; Lerfiana, Ema; Mekkawati (Pusat Riset dan Inovasi Nasional, 2021)
The goal of the study was to see if using authentic material helped students enhance their vocabulary. With a one-group pretest and posttest design, the researcher used the pre-experimental approach. The study's participants were students in their first year of MA Nurul As'adiyah Callaccu's academic year 2019/2020. The study included a total of 35 students as a sample. Cluster random sampling was used to collect the data. The information was gathered through vocabulary exams (pretest and posttest). The researcher utilized t-test analysis to see if using authentic material helped students improve their vocabulary. The data analysis revealed that the difference between the pretest and posttest was considerable. The value of sig (2-tailed) was smaller than the value of (a) = 0.05 (0.00<0.05), as shown by the statistical calculation. Based on the outcomes of the study, the researcher concludes that using authentic material in the first year of MA Nurul As'adiyah Callacu can help students improve their vocabulary.